POPULATION DYNAMICS OF METAZOAN PARASITES OF MARINE THREADFIN FISH, POLYDACTYLUS SEXTARIUS (BLOCH AND SCHNEIDER, 1801) FROM VISAKHAPATNAM COAST, BAY OF BENGAL - MANI GUDIVADA,; VANKARA, ANU PRASANNA (The Bioscan, 2010)
Population dynamics of metazoan parasites of marine threadfin fish, Polydactylus sextarius have been studied for two consecutive years 2005-2006 and 2006-2007 from Visakhapatnam (17.67º’N and 83.32º’E), in the coastal zone of Bay of Bengal, Andhra Pradesh. A total of 676 host species were examined, of which 563 hosts were found to be infected. 24 species of metazoan parasites were collected, comprising 2 monogenetic trematodes, 11 digenetic trematodes, 2 cestode larvae, 1 nematode, 4 Acanthocephalans, 3 copepods and 1 isopod. The ecological parameters like prevalence, mean intensity and mean abundance were calculated to determine the abundance of parasitic species. This study was carried for both overall and groupwise parasitizations. The larval cestodes dominate the parasitic community and the digenetic trematodes occupy the second position. Seasonal variation on parasitization, the relationship between host size and prevalence of infection were studied but the host sex was not taken into consideration due to protandrous nature of the host.